2021
DOI: 10.1111/ajt.16425
|View full text |Cite
|
Sign up to set email alerts
|

Optimal donation of kidney transplants after controlled circulatory death

Abstract: Controlled donation after circulatory death (cDCD) is used for “extended criteria” donors with poorer kidney transplant outcomes. The French cDCD program started in 2015 and is characterized by normothermic regional perfusion, hypothermic machine perfusion, and short cold ischemia time. We compared the outcomes of kidney transplantation from cDCD and brain‐dead (DBD) donors, matching cDCD and DBD kidney transplants by propensity scoring for donor and recipient characteristics. The matching process retained 442… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…This may translate into 5 additional years of graft life for the recipients. 21,22 Recent French data 13 suggest that recipients of NRP kidneys have comparable 1-y outcomes with recipients of DBD kidneys, albeit the French mandate ex situ hypothermic machine perfusion of kidneys following NRP, something that is not routine in the United Kingdom and was not done in any NRP donor kidney at the point of donation in this series. In our study, we have noted a slight reduction in the rate of primary nonfunction plus a notable decrease in DGF rate from 31% for non-NRP cDCD transplants to 23% when NRP was used.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This may translate into 5 additional years of graft life for the recipients. 21,22 Recent French data 13 suggest that recipients of NRP kidneys have comparable 1-y outcomes with recipients of DBD kidneys, albeit the French mandate ex situ hypothermic machine perfusion of kidneys following NRP, something that is not routine in the United Kingdom and was not done in any NRP donor kidney at the point of donation in this series. In our study, we have noted a slight reduction in the rate of primary nonfunction plus a notable decrease in DGF rate from 31% for non-NRP cDCD transplants to 23% when NRP was used.…”
Section: Discussionmentioning
confidence: 86%
“…9,10,14 Data on the impact of NRP on organ utilization and the outcomes of renal and pancreas transplantation are scarce. [13][14][15] This study compared the utilization rates and clinical outcomes of organs offered for transplantation and recovered using NRP with a contemporaneous UK cohort of cDCD donors undergoing standard organ recovery over a 9-y period, where at least 1 abdominal organ was accepted for transplant. We have shown that NRP is an independent factor in increasing organ utilization for all abdominal organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled donation after circulatory death (cDCD) refers to organ donation from patients whose death is defined using circulatory criteria after the planned withdrawal of lifesustaining treatments (WLST) (1). The scarcity of donor organs and the good transplantation outcomes (2)(3)(4) legitimately support the development of this type of donation (5)(6)(7) in a context where WLST decisions occur more and more frequently in intensive care units (ICU) worldwide (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the scarcity of donor organs and the good transplantation outcomes [ 5 , 6 ] legitimately support the development of cDCD in a context where WLST decisions occurs more and more frequently in ICUs worldwide [ 7 ]. This development is limited by technical and organizational aspects, in particular related to the systematic use of normothermic regional perfusion (NRP), which requires technology (NRP device) and expertise (NRP settings and vessels cannulation) not available in all hospitals.…”
mentioning
confidence: 99%